An in depth characterization of the spectroscopic properties and laser action of 10 at% Yb doped Y3ScxAl5-xO12 (x = 0.25, 0.5, 1.0, 1.5) transparent ceramics. Issue 11 (1st August 2020) - Toci, Guido; Pirri, Angela; Patrizi, Barbara; Feng, Yagang; Xie, Tengfei; Yang, Zhaoxiang; Li, Jiang; Vannini, Matteo
Abstract: We report on the spectroscopic and laser emission properties of 10 at% Yb:Y3 Scx Al5-x O12 (Yb:YSAG) ceramic varying the amount of Sc (x) ranging from x  = 0.25 to x  = 1.5. The samples were fabricated by a solid state reaction method followed by vacuum sintering and annealing in air. The spectroscopic investigation has evidenced an increased broadening in both the absorption and the emission spectra for increasing Sc content, as well as an extension of lifetime at increased Sc content. Concerning the laser performance, the maximum slope efficiency, i.e. 76.6%, was obtained with the sample with x  = 0.25 while the largest tuning range, i.e. 81 nm, with the sample having the highest concentration of Sc ions ( x  = 1.5); a steady broadening in the tuning bandwidth for increasing Scandium content was measured.